The Interplay of Internet of Things (IoT) and Green Economy: A Bibliometric Analysis of Indian and Global Trends - Meenakshee Pandey, (International Journal of Scientific Research in Science and Technology, 2025)
Internet of Things (IoT) technologies offer an increasing role in green economies across the world through facilitating environmental conservation and responsible use of natural resources. IoT technologies offer prospects for addressing environmental issues such as pollution, water scarcity, and unsustainable urban expansion in India. This study uses systematic descriptive and bibliometric methods to analyse Scopus data to examine India's research development in the area of the linkage between the green economy and the Internet of Things (IoT). The findings suggest that China dominates the world in research collaborations and citation impact in the context of the nexus between IoT and the Green Economy topic, whereas India demonstrates a substantial research endeavour, yet it is not as per the current need. This underlines the necessity that India must increase IoT and green economy research to effectively leverage IoT technology to reduce environmental problems and improve environmentally supportive economic pathways for green economic growth.
Keywords: Internet of Things (IOT); Green Economy (GE); SCOPUS Database; Bibliometric Analysis; India